A pluralistic evaluation of services for women with long-term mental health problems - Owen, Sara (1999)
This thesis presents a pluralistic evaluation of the services provided for women with long-term mental health problems receiving care and support within the Rehabilitation and Community Care Service (RCCS) in Nottingham. The thesis is grounded in data collected within an evaluative research framework and developed within a mental health policy framework. The evaluation consists of a series of six studies which are informed by a set of evaluation criteria which reflect a range of stakeholder perspectives. The first study examines the socio-demographic and psychiatric characteristics, social functioning and service use of all 480 clients registered with the RCCS. The clients' characteristics are similar to those described in previous studies. There are some• differences between the men and the women, notably that the women are under-represented amongst those receiving a high level of input from the services. The second and third studies explore the extent and adequacy of services for women with long-term mental health problems in the Nottingham district through interviews with small groups of service providers working throughout the RCCS, and through a postal questionnaire to thirty eight organizations outside the RCCS. Special provision made for women is patchy, and there is no overall strategy to ensure even provision throughout the RCCS and the organizations outside the service, or co-ordination between them. The fourth study assesses the initial socio-demographic and psychiatric characteristics, social functioning, satisfaction with services, and quality of life of 31 men and 10 women at their time of entry into the RCCS and one year later, and their use of all services during this time. The women experienced a greater number of life events than the men, changed their accommodation more frequently, and the services appear to be less responsive to their particular needs. The outcome after twelve months shows that overall the social functioning and quality of life of the clients had not improved. There were some changes in service use, notably the greater number of clients living independently. The fifth study uses semi-structured interviews to explore the problems service providers experience in planning and delivering a service to women with long-term mental health problems. Two overriding themes emerge from the data; service providers as empathic women, and service providers as professionals, which lead them to experience a conflict between respecting the rights of women with long-term mental health problems and protecting them. The final study uses focus groups to explore the impact of mental health problems on the lives of women with long-term mental health problems, and their views of the services they currently receive. Three themes emerge from the data; loss, hope and views about services. Despite overwhelming losses many of the women retain hopes and aspirations for the future. The women identify negative and positive aspects of the services they are receiving together with some recommendations for change. The thesis contributes to current knowledge about the experiences of women with long-term mental health problems in a number of ways. First, the findings of the six studies which make up the evaluation highlight the ways in which the RCCS was successful in meeting these women's needs, and the many gaps in existing provision. Second, women with long-term mental health problems can give coherent and comprehensive accounts of their experiences. Third, the findings illuminate the current predicament of women with long-term mental health problems which is that they remain excluded and marginalised from the communities where they are now living.